BINTAN ISLAND TOURISM MARKETING STRATEGY BY TOUR DE BINTAN - Enggartiasto, Ariobimo; Safitri, Karin Amelia (Journal of Indonesian Tourism and Policy Studies, 2019)
This Journal discusses the analysis of the implementation of marketing strategies carried out in Bintan Island. In this Journal also explained the obstacles that occur in marketing tourism in Bintan Island. This Journal was compiled using data collection and interview research. The results of the research and interviews explained that the strategy carried out to market tourism destinations in Bintan Island was good but there were still obstacles in the marketing process.